Society Readiness Index using Blockchain Technology in Zakat Payments: Technology Readiness Index Approach - A. Jajang W. Mahri; Ripan Hermawan; Ipan Ahmad (Review of Islamic Economics and Finance, 2023)
AbstractPurpose - To find out the index and segmentation of West Java society in their readiness to accept blockchain technology in zakat payments. Design/Methodology/Approach – The testing method used in this research is a quantitative method with a descriptive approach. Data analysis techniques use TRI to find out the magnitude of the technology acceptance readiness index and the categorization formula to determine the segmentation of community groups in their readiness to accept blockchain technology. The sample used was 145 Moslem communities in West Java. Results – The results of the study show that the readiness of the people of West Java to use blockchain technology for zakat payments is at high technology readiness. The attitude of the people of West Java to the acceptance of blockchain technology for zakat payments is in the pioneer group or groups who have a great desire to use blockchain technology for zakat payments, but if the technology does not meet expectations or is difficult to use, it will be easy to abandon and difficult to develop.Research Limitation/ Implication – The research conducted is still limited only to determine the index or level of readiness to accept technology. In addition, public literacy regarding blockchain technology is still lacking, so filling out the questionnaire is based on the respondent's experience in using digital transactions. The results obtained are not fully optimal. For further research, it is necessary to identify what factors influence people's readiness to accept blockchain technology in zakat payments in order to realize a better development of blockchain zakat technology in the future.Originality/Value – This research combines two disciplines, namely technology and Islamic economics to obtain new research findings, besides that, the use of the technology studied is the latest and most up-to-date technology for zakat management.Keywords – Technology Readiness, Blockchain Technology, Technology Acceptance Segmentation, Zakat, West Java.